Modeling the links between young swimmers` performance: Energetic and biomechanic profiles - Barbosa, T. M.; Costa, M.; Marinho, D. A.; Coelho, J.; Moreira, M.; Silva, A. J. (Pediatric Exercise Science, 2010)
The aim was to develop a path-flow analysis model for young swimmers` performance based on biomechanical and energetic parameters, using structural equation modeling. Thirty-eight male young swimmers served as subjects. Performance was assessed by the 200-m freestyle event. For biomechanical assessment the stroke length, the stroke frequency and the swimming velocity were analyzed. Energetics assessment included the critical velocity, the stroke index and the propulsive efficiency. The confirmatory model explained 79% of swimming performance after deleting the stroke index-performance path, which was nonsignificant (SRMR = 0.06). As a conclusion, the model is appropriate to explain performance in young swimmers.